Twenty-Seven Cases of Marjolins Ulcer; An Institutional Experience on Diagnosis, Treatment and Outcomes - BR, Kiran Kumar; Shankar, Amritha Prabha; Narayanan, Geeta S; M S, Ganesh (Asian Pacific Journal of Cancer Biology, 2024)
Purpose: Marjolins ulcer is a malignant transformation that arises from chronic ulcers or previously traumatized scar that occur usually after burns. To study the clinicopathological characteristics and treatment outcomes of Marjolins ulcer at our institute. Materials and methods: Retrospective analysis of all Marjolins ulcer patients presented to our department from 2018 to 2021 was done. A total of 27 patients of all age groups were included in the study. All the information regarding the diagnosis, treatment and outcome details were collected and analysed. Results: Most of the patients were in the 5th decade of life with an overall male preponderance. The most common cause for Marjolin ulcer was Burns Scar. The mean latency period for the development of Marjolins ulcer was 11 years. Squamous cell carcinoma was the most common histological subtype. 18.5% patients received Adjuvant radiotherapy. At the median follow up of 14 months, one patient presented with locoregional relapse. Conclusion: Chronic non-ulcers that do not respond to treatment should be carefully examined by multidisciplinary team for malignant transformation. Surgery is the mainstay of treatment and Adjuvant Radiotherapy should be considered in high-risk cases to reduce locoregional recurrence. Tumour size and nodal involvement are the main predictors of locoregional relapse.